2013
DOI: 10.1111/pme.12063
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Angiotensin II Type 2 Receptor (AT2R) Antagonists as Novel Analgesics for Neuropathic Pain: Comparative Pharmacokinetics, Radioligand Binding, and Efficacy in Rats

Abstract: The small molecule AT₂R antagonist, EMA401, is in clinical development as a novel analgesic for the relief of neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
117
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(126 citation statements)
references
References 20 publications
9
117
0
Order By: Relevance
“…bolus doses of EMA200, EMA300, and EMA400 evoked dose-dependent mechanical hypersensitivity in the ipsilateral (injured side) hindpaws. 41 The ED 50 s for EMA200, EMA300, and EMA400 for evoking pain relief were 3.2, 0.78, and 0.01 mg/kg, respectively, showing that EMA400 is ;250-fold more potent than EMA200 and ;60-fold more potent than EMA300 in this model. 41 …”
Section: Chronic Constriction Injury Of the Sciatic Nerve In The Ratmentioning
confidence: 96%
See 2 more Smart Citations
“…bolus doses of EMA200, EMA300, and EMA400 evoked dose-dependent mechanical hypersensitivity in the ipsilateral (injured side) hindpaws. 41 The ED 50 s for EMA200, EMA300, and EMA400 for evoking pain relief were 3.2, 0.78, and 0.01 mg/kg, respectively, showing that EMA400 is ;250-fold more potent than EMA200 and ;60-fold more potent than EMA300 in this model. 41 …”
Section: Chronic Constriction Injury Of the Sciatic Nerve In The Ratmentioning
confidence: 96%
“…41 The 10,000-fold specificity of EMA401 at the AT 2 over the AT 1 receptor is due to its very low binding affinity at rat and human AT 1 receptors (IC 50 values .50 mM) ( Table 1). 41 5. Analgesic efficacy in rodent models of peripheral neuropathic pain…”
Section: Radioligand Bindingmentioning
confidence: 97%
See 1 more Smart Citation
“…AT2 receptor became new therapeutic target for the treatment of neuropathic pain. A few molecules like PD123319 [16,17] and EMA401 [18] are in clinical trials but treatment is limited due to poor efficacy and unfavourable side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Small molecule angiotensin II type 2 receptor (AT 2 R) antagonists have also been proposed as analgesics for neuropathic pain [Smith et al 2013]. Most recently, a high-profile double-blind placebo-controlled trial demonstrated the efficacy of EMA401, a novel AT 2 R antagonist, in the treatment of PHN and this drug remains in development as a therapeutic agent for neuropathic pain [Rice et al 2014].…”
Section: Future Directionsmentioning
confidence: 99%